Neuroinflammation and apoptosis after surgery for a rat model of double-level cervical cord compression. (July 2022) - Yao, Min; Li, Gan; Pu, Pei-min; Zhou, Long-yun; Li, Zhuo-yao; Liu, Shu-fen; Sng, Kim Sia; Zheng, Zhong; Song, Yong-jia; Zhu, Ke; Wang, Yong-jun; Cui, Xue-jun
Abstract: Introduction: Cervical spondylotic myelopathy (CSM) is the most prevalent type of non-traumatic spinal cord injury. The pathological process of CSM is relatively complicated. Most of the chronic cervical cord compression animal models established using hydrophilic expanding polymer are single-segment compression, which was deviated from clinical practice with double-segment or multi-segment compression. This study aims to better mimic the actual clinical compression by using a new type of hydrophilic expanding polymer to establish an animal model of double-level cervical cord compression. Materials and methods: Progressive cord compression was done with implantation of polyvinyl alcohol-polyacrylamide hydrogel in the spinal canal at the C3-4 and C5-6 levels. Sprague-Dawley rats ( n = 32) were divided into three groups: sham (no compression, n = 12) and screw compression group ( n = 8), and hydrogel compression group ( n = 12). Functional deficits were characterized using motor function scores, forelimb grip strength, hindlimb pain threshold, and gait analysis, while compression was imaged with magnetic resonance imaging. The apoptosis, inflammation, and demyelination were assessed by hematoxylin and eosin staining, Luxol fast blue staining, TUNEL assay, immunofluorescence staining, and Western blot analysis. Results: Motor function scores for rats with cervical cord hydrogel compression were significantly decline in motor function scores, an increase in allodynia, neurons and oligodendrocytes apoptosis related to B cell lymphoma-2 (Bcl-2)/Bcl-2 associated X (Bax)/cleaved caspase-3, and impaired axonal conduction, as well as neuroinflammation zone related to microglia or macrophages aggregation related to the nucleotide-binding domain, leucine-rich-repeat-containing family, pyrin domain-containing 3 (NLRP3) inflammasome activation, and activation of astrocytes, as well as oxidative stress were observed. Conclusion: We believe that this model utilizing compression on double-level cervical cord will allow researchers to investigate of translationally relevant therapeutic methods for CSM. Highlights: A novel animal model of double-level cervical cord compression can better mimic the actual CSM by using a hydrophilic expanding polymer. This compression model increase the apoptosis of neurons and oligodendrocytes at the compression site. The NLRP3 inflammasome increased after compression, resulting in increased spinal nerve inflammation.